2015
DOI: 10.1099/jgv.0.000278
|View full text |Cite
|
Sign up to set email alerts
|

Secretion of dengue virus envelope protein ectodomain from mammalian cells is dependent on domain II serotype and affects the immune response upon DNA vaccination

Abstract: Dengue virus (DENV) is currently among the most important human pathogens and affects millions of people throughout the tropical and subtropical regions of the world. Although it has been a World Health Organization priority for several years, there is still no efficient vaccine available to prevent infection. The envelope glycoprotein (E), exposed on the surface on infective viral particles, is the main target of neutralizing antibodies. For this reason it has been used as the antigen of choice for vaccine de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 82 publications
(83 reference statements)
2
17
0
Order By: Relevance
“…We have previously reported a detailed analysis of the secretory profile of recombinant E derived from the different DENV serotypes in mammalian cells and shown that DENV2 E ectodomain (2sE) undergoes different folding depending on temperature 36 . Here we have further investigated the role of temperature and PrM in the production and secretion of sE from DENV and ZIKV in transfected HEK293T cells, using constructs encoding sE alone or sE and the viral proteins PrM or only M (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We have previously reported a detailed analysis of the secretory profile of recombinant E derived from the different DENV serotypes in mammalian cells and shown that DENV2 E ectodomain (2sE) undergoes different folding depending on temperature 36 . Here we have further investigated the role of temperature and PrM in the production and secretion of sE from DENV and ZIKV in transfected HEK293T cells, using constructs encoding sE alone or sE and the viral proteins PrM or only M (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The same set of reagents was used for cytofluorimetric analysis of cell membrane display of sE-cvD ((m)sE-cvD), achieved by fusing the trans-membrane and cytosolic tail of the type-I trans-membrane protein MHC-Iα at the C-terminus of sE, as previously reported 36 . Transfected cells were incubated with the set of mAbs following expression of (m)sE-cvD (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…22 Removal of the transmembrane domain also provided superior immunogenicity in vivo compared with the full-length F gene. 43,44 Expression of the immuno-dominant epitope of the HRSV M2 protein (residues 82-90) in conjunction with the F or G proteins induced a potent CTL response and a balanced Th1/Th2 response in mice.…”
Section: Discussionmentioning
confidence: 99%